2013
DOI: 10.1007/s00253-013-5341-8
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial structure and spatiotemporal distribution in a horizontal subsurface flow constructed wetland

Abstract: In this study, bacterial community structure in a horizontal subsurface flow constructed wetland (HSF-CW) planted with Phragmites australis was investigated using the 16S rRNA cloning-sequencing technique. Two layer depths were considered: the rhizosphere zone (RH) and the deep-layer zone (DL) in different sampling periods. Bacteria-specific primers 008F and 1492R were used to amplify the 16S rRNA genes and construct six clone libraries. A total of 1,284 individual sequences were used to assess the HSF-CW dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 41 publications
2
11
0
Order By: Relevance
“…All soils were predominated by sequences of the class Proteobacteria. This finding is consistent with previous reports on the rhizosphere of P. australis (Li et al 2013;Bouali et al 2014b). Proteobacteria constituted 24-70% of the total sequences in our samples as well as in the rhizosphere of P. australis from other oil-free and oil-polluted wetlands (Bouali et al 2014b;Tian et al 2014).…”
Section: Proteobacteria In Rhizosphere Soilssupporting
confidence: 93%
See 1 more Smart Citation
“…All soils were predominated by sequences of the class Proteobacteria. This finding is consistent with previous reports on the rhizosphere of P. australis (Li et al 2013;Bouali et al 2014b). Proteobacteria constituted 24-70% of the total sequences in our samples as well as in the rhizosphere of P. australis from other oil-free and oil-polluted wetlands (Bouali et al 2014b;Tian et al 2014).…”
Section: Proteobacteria In Rhizosphere Soilssupporting
confidence: 93%
“…This finding is consistent with previous reports on the rhizosphere of P. australis (Li et al 2013;Bouali et al 2014b). Proteobacteria constituted 24-70% of the total sequences in our samples as well as in the rhizosphere of P. australis from other oil-free and oil-polluted wetlands (Bouali et al 2014b;Tian et al 2014). and Leclercia were shown to degrade low and even high molecular weight hydrocarbons (Cébron et al 2011;Chandra et al 2012).…”
Section: Proteobacteria In Rhizosphere Soilssupporting
confidence: 93%
“…The dominance of Proteobacteria has been found in natural wetlands (Ansola et al 2014;Liu et al 2014b), wastewater CW systems (Ansola et al 2014;Bouali et al 2014;Huang et al 2013), and biofilters treating surface water (Feng et al 2013a;Liao et al 2013b). Moreover, a previous study using DGGE analysis also suggested the dominance of proteobacterial organisms in a large-scale CW system Fig.…”
Section: Bacterial Community Structurementioning
confidence: 89%
“…Previous studies using traditional molecular biology approaches [e.g., denaturing gradient gel electrophoresis (DGGE), terminal restriction fragment length polymorphism (TRFLP), and clone library analysis] have greatly aided in our understanding of microbial community structure in CW ecosystem (Arroyo et al 2013;Elsayed et al 2014;Iasur-Kruh et al 2010;Morato et al 2014). A variety of factors have also been found to influence the structure of CW microbial community, such as layer depth (Bouali et al 2014;Iasur-Kruh et al 2010), operational time (Bouali et al 2014), plant type (Menon et al 2013), plant species richness , plant development (Zhao et al 2012), wastewater quality characteristics (Chang et al 2015;Zhao et al 2012), flow (Arroyo et al 2013), and water depth (Morato et al 2014). These previous studies mainly focused on CW systems treating industrial and municipal wastewater, yet microbial community in CW systems purifying polluted surface water has received little attention.…”
Section: Introductionmentioning
confidence: 99%
“…Ibekwe and co-workers [63] assessed the bacterial community dynamics using pyrosequencing in surface flow CWs but only with three sampling events over time. The other studies on temporal dynamics of microbial communities in HSSF CWs are mostly based on PCR-DGGE ( [64], few sampling events over time) and 16S rDNA cloning approach ( [65], three sampling events). The temporal aspect has not been taken into account in the data analysis in previous studies.…”
Section: Discussionmentioning
confidence: 99%